An Efficient TDOA-Based Localization Algorithm without Synchronization between Base Stations - Sangdeok Kim; Jong-Wha Chong (International Journal of Distributed Sensor Networks)
An efficient localization algorithm is proposed by utilizing the time difference of arrival (TDOA) without synchronization between base stations. Generally, a TDOA-based localization algorithm requires synchronization between base stations in order to improve the accuracy of localization. Hence, correlations using wideband signals or wire connections between base stations have been used to synchronize the base stations; however, these approaches result in additional operating costs. Thus, the proposed algorithm does not require synchronization between base stations. The TDOA equations are derived by continuously varying the locations of the source and the location of a base station. The number of packets necessary for localization is also reduced. The localization performance of the proposed algorithm is verified with Monte-Carlo simulations.